Development and validation of the Aktan–Akar risk-taking scale - Akar, Atanur; Aktan, Timuçin (Journal of Dependence, 2026)
Objective: The aim of this study was to examine the psychometric properties of the Aktan–Akar Risk-Taking Scale, which was developed to assess university students’ risk-taking tendencies across different life domains. Method: Data were collected from 395 university students (18–25 years; M = 20.57, SD = 1.72). An item pool was generated and refined based on expert and student evaluations. Construct validity was examined via exploratory and confirmatory factor analyses; reliability via Cronbach’s alpha. Convergent and divergent validity were evaluated through inter-subscale correlations and associations with the Rathus Assertiveness Scale. Criterion-related validity was assessed through correlations with dispositional self-control, gender role self-concept, and core gender identity. Domain differences and associations with demographic variables were also analyzed. Results: The EFA revealed a four-factor structure for the Risk-Taking Scale, explaining 38.40% of the variance, with domains of Physical–Safety, Academic–Ethical, social media–Entrepreneurial, and Financial–Debt risks. CFA confirmed this model, and subscale alphas ranged from .67 to .72. Correlations among subscales and with assertiveness supported convergent and divergent validity. Lower dispositional self-control was associated with greater risk taking, and risk taking in different domains reflected gender role expectations. Conclusion: Risk-Taking Scale is a valid and reliable measurement tool for assessing domain-specific risk-taking tendencies among university students. The scale may be used in research and applied settings to examine the psychosocial determinants of risk-taking behaviors and to support preventive intervention efforts.